ANALISIS FAKTOR – FAKTOR PENERIMAAN DAN PENGGUNAAN APLIKASI SEABANK DAN BANK JAGO DENGAN MODEL UTAUT2 - Agil, Helvina Agil; Rahma, Rahma Fitria; Zalfie, Zalfie Ardian (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2025)
In recent years, banking in Indonesia has undergone significant transformation through the use of technology, as reflected in the increase in digital transactions, which reached Rp15,881.53 trillion, a year-on-year growth of 16.15%. This study employs the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model to analyze the factors influencing the acceptance and use of Seabank and Bank Jago digital banking applications. This study is a quantitative research using a survey method involving 632 student respondents in North Sumatra up to Lhokseumawe, analyzed using descriptive statistics and hypothesis testing based on Structural Equation Modeling (SEM). The results of the descriptive statistical analysis showed that the average user response to the Seabank app was 87.02% and Bank Jago was 84.82%, both falling into the “strongly agree” category, indicating a positive response. Hypothesis analysis revealed that social influence, facilitating conditions, price value, habits, behavioral intention, and usage behavior significantly influence the acceptance of the Seabank app. For Bank Jago, the significant influencing factors are social influence, price value, habits, behavioral intention, and usage behavior. The findings of this study confirm the applicability of UTAUT2 in the context of digital banking in Indonesia and provide practical insights for app developers and policymakers to encourage the adoption of digital banking services.